THE IMPORTANCE OF DIET IN PATIENTS WITH CIIRHOSIS OF THE LIVER - Istamova Sitora Ne`matovna; Xaqberdiyeva Iroda Orifjonovna (Web of Journals Publishing, 2025)
Cirrhosis of the liver is a chronic progressive liver disease with varying degrees of symptoms of functional liver failure. From a morphological point of view, the disease is characterized by necrosis of hepatocytes and their replacement with connective tissue, as well as the formation of regenerator nodes and restructuring of the entire structure of the liver. In economically developed countries, cirrhosis is one of the 6 main causes of death of patients between the ages of 30 and 60, accounting for 20-35 cases per 100,000 population. Every year in the World, 45 million people die from developing liver viral cirrhosis and hepatocellular carcinoma against the background of a carrier of the hepatitis B virus.
Keywords: Cirrhosis of the liver, hepatitis, hepatoprotector, necrosis, probiotics, ascites, carcinoma, dyspeptic syndrome.